Relokasi Hiposenter dan Mekanisme Sumber Gempa Bumi Danau Poso 24 Juli 2025 (Mb 6,2) di Sulawesi Tengah, Indonesia - Fajar Dwinahdi; Dimas Salomo Januarianto Sianipar; Indah Fajerianti; Gatut Daniarsyad (Mataram University, 2026)
An earthquake of Mb 6.2 shook the Lake Poso area, Central Sulawesi, on July 24, 2025 at 13:06:59 WIB. This study aims to examine the characteristics of the earthquake source through two approaches: hypocenter relocation using the double-difference (hypoDD) method and focal mechanism inversion (moment tensor) using regional waveform data. A total of 458 events in the January-November 2025 period were relocated, resulting in 445 relocated events (97.2%), the majority (432 events) of which were concentrated in one main cluster with an average residual RMS of 0.32 seconds. The main earthquake shifted 4.5 km to the west and shallow from 10 km to 4.45 km. The inversion of the moment tensor results in a Deviatoric solution with a depth of 5.50 Mw, a depth of 7 km, and a left-lateral oblique mechanism with minor normal components (fault plane: strike 298°, dip 61°, rake −19°). The orientation of the fault plane (WNW–ESE) is parallel to the structure that caused the Poso earthquake on May 29, 2017 Mw6.6 (Tokorondo Fault), but the different slip characters indicate the possibility of oblique strain partitions along the eastern extensional zone of Central Sulawesi. These results make an important contribution to the understanding of regional seismotectonics and earthquake risk mitigation around Lake Poso.